地方政府教育課責系統現況與成效探究 Educational Accountability System in Local Government: Current Conditions and Impact - 賴彥全 Yen-Chywan Lai; 王麗雲 Li-Yun Wang (National Taiwan Normal University, 2014)
受新右派主義與新公共管理思潮影響，政治治理（governance）納入績效回應等觀念，對於公部門課責（accountability）需求高漲，以確保官僚組織的高績效與高回應性。本研究以地方縣市政府課責系統為焦點，以活化課程為研究對象，探討地方教育課責系統之運作途徑、效果以及影響因素。先由文獻歸納課責五大機制－科層課責、法律課責、政治課責、專業課責、社會課責，再透過個案研究，以臺北縣（現為新北市）活化課程為例，透過文件分析、訪談，探討縣市政府之課責系統。結果發現，科層課責因法制及政治因素成效不彰，法律課責以經費掌控為主政治性強，政治課責具影響力但與選舉連結有限，專業課責受文化因素影響並不顯著，社會課責力道強但受壓力團體影響。各課責機制間存在相互影響，以及政治考量介入之情形。 The emerging influences of the "New Right" and the "New Public Management" have prompted the government to incorporate additional ideas of market principles and responsiveness in their management. A public accountability system is established when the demands for efficiency and answerability increase. Because local governments are currently the major providers of education, examining how the educational accountability system functions in local government is crucial. The concepts, types, and operations of accountability systems in local governments were examined. Five types of accountability system, namely hierarchical accountability, legal accountability, political accountability, professional accountability, and social accountability, were considered. Language Enrichment Curriculum of Taipei County (now New Taipei City) was used as the case for study. Document analysis and interviews were used to collect information on how the five types of accountability system functioned in this case. Hierarchical accountability lacks the coercive power it is intended to exert. Legal accountability relies mainly on financial control and is often subjected to political intervention. Political accountability has limited influence because of its poor connection with elections. Professional accountability is weak for cultural reasons. Social accountability is vigorous but mainly dominated by interest groups. Conflicts among different accountability systems are often observed and political interventions are common. In addition, suggestions are provided.